Poly(dA:dT) Suppresses HSV-2 Infection of Human Cervical Epithelial Cells Through RIG-I Activation - Shao, Dan-Dan; Meng, Feng-Zhen; Liu, Yu; Xu, Xi-Qiu; Wang, Xu; Hu, Wen-Hui; Hou, Wei; Ho, Wen-Zhe (Frontiers in Immunology, 2021)
Epithelial cells of the female reproductive tract (FRT) participate in the initial innate immunity against viral infections. Poly(dA:dT) is a synthetic analog of B form double-stranded (ds) DNA which can be sensed by the cytosolic RNA sensor retinoic acid-inducible gene-I (RIG-I) and activates the interferon (IFN) signaling pathway eliciting an intracellular immune response to control virus replication. Here we investigated whether poly(dA:dT) could inhibit herpes simplex virus type 2 (HSV-2) infection of human cervical epithelial cells (End1/E6E7). We demonstrated that poly(dA:dT) treatment of End1/E6E7 cells could significantly inhibit HSV-2 infection. Mechanistically, poly(dA:dT) treatment of the cells induced the expression of the intracellular IFNs and the multiple antiviral IFN-stimulated genes (ISGs), including IFN-stimulated gene 15 (ISG15), IFN-stimulated gene 56 (ISG56), 2'-5'-oligoadenylate synthetase 1 (OAS1), 2'-5'-oligoadenylate synthetase 2 (OAS2), myxovirus resistance protein A (MxA), myxovirus resistance protein B (MxB), virus inhibitory protein, endoplasmic reticulum-associated, IFN-inducible (Viperin) and guanylate binding protein 5 (GBP5). Further investigation showed that the activation of RIG-I was largely responsible for poly(dA:dT)-mediated HSV-2 inhibition and IFN/ISGs induction in the cervical epithelial cells, as RIG-I knockout abolished the poly(dA:dT) actions. These observations demonstrate the importance for design and development of AT-rich dsDNA-based intervention strategies to control HSV-2 mucosal transmission in FRT.